Laboratory impact experiments with decimeter-to meter-scale targets to measure momentum enhancement. (15th November 2019) - Durda, Daniel D.; Walker, James D.; Chocron, Sidney; Housen, Kevin R.; Grosch, Donald J.; Marchi, Simone; Flynn, George J.; Strait, Melissa M.
Abstract: Among the more technically practical methods of deflecting a potentially hazardous object (PHO) is kinetic impact, whereby the momentum change imparted to the object by the cratering impact of a targeted spacecraft or other projectile affects the required minor orbital change to avert impending disaster. The ratio of the momentum change of the target to the impact momentum is commonly denoted as β, the momentum enhancement factor. Knowledge of what values of β to expect for impacts into near-Earth asteroids (NEAs) in the range of size and composition representative of objects in the known population of PHOs is thus crucial in designing and planning for mitigation strategies focused on the kinetic impact method. We present results of laboratory impact experiments, conducted with targets ranging in size from decimeter to meter size scales and measuring β in the process. Our impact experiments utilize the Southwest Research Institute's (SwRI) 50-mm powder gun, which can fire up to 260-g mass projectiles at speeds of 2 km/s, supplemented by smaller-scale experiments using the NASA Ames Vertical Gun Range (AVGR) as necessary to study a parameter space that includes projectile mass, speed, composition, impact angle as well as target mass composition and temperature. Targets are mounted to allow recoil (on a conventional ballistic pendulum) and all impact experiments are documented by high-speed video allowing the required analysis to quantify impact outcome and target recoil. To date we have completed 29 small-scale shots at the AVGR and 24 large-scale shots with the SwRI 50-mm powder gun. AVGR experiments include 13 shots into 10.2-cm and 15.2-cm right cylinders composed of a plaster-sand mix as a porous silicate asteroid analog, two shots into 15.2-cm pumice cubes, and 14 shots into 10.2-cm right cylinders of an iron-nickel alloy approximating the composition of iron meteorites. β values of 1–2 and 1.3 were obtained for the plaster-sand mix and the pumice, respectively, and 1.7–2 for the iron-nickel shots, performed at temperatures of about 297 K and 149 K, thus spanning the ductile to-brittle fracture transition. For the metal target shots we see what appears to be a trend to higher β for higher speed shots and for the cryo shots. SwRI 50-mm powder gun shots were conducted with large pieces of pumice, concrete, and sandstone impacted with 2.54-cm and 4.45-cm aluminum projectiles at impact speeds of 2.0 km/s. Although the pumice targets do not show a size scale effect and data from the sandstone shots are still being analyzed, the concrete material does show a significant size scale effect. Additional shots are planned for meter-scale targets composed of the same plaster-sand mix previously shot at decimeter scale at the AVGR. Highlights: Laboratory impact experiments conducted with targets ranging in size from decimeter to meter size scales. Silicate and iron-nickel alloy targets. Momentum enhancement factor, β, values of 1–2 were obtained for silicate targets, and 1.7–2 for iron-nickel targets. Metal target shots display an apparent trend to higher β for higher speed shots and for low-temperature shots. Concrete material shows a significant size scale effect.